2020
DOI: 10.1186/s13054-020-03079-y
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-D: a novel biomarker for detection of COVID-19 progression

Abstract: As the coronavirus 2019 (COVID-19) continues to spread globally, hundreds of thousands have been infected, among whom approximately 15% of COVID-19 patients develop severe disease, and 5 to 6% are critically ill [1]. Critical patients of COVID-19 have a dramatically higher case fatality rate than severe cases. Thus, it is increasingly urgent to develop early and effective predictors to distinguish critical patients from severe patients. Storms of inflammatory cytokines and blood clots were reported to associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 5 publications
5
89
0
Order By: Relevance
“…Among the VEGF system, VEGF-D [ 28 ], and sFLT-1 [ 29 ] have been discussed in the pathophysiology of COVID-19. Kong et al reported a positive correlation between VEGF-D: a still not fully understood member of the VEGF family – and disease severity in COVID-19 patients [ 28 ]. Surprisingly, we found a clear negative correlation between VEGF-D and SOFA score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the VEGF system, VEGF-D [ 28 ], and sFLT-1 [ 29 ] have been discussed in the pathophysiology of COVID-19. Kong et al reported a positive correlation between VEGF-D: a still not fully understood member of the VEGF family – and disease severity in COVID-19 patients [ 28 ]. Surprisingly, we found a clear negative correlation between VEGF-D and SOFA score.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found a clear negative correlation between VEGF-D and SOFA score. A reason for this discrepancy could be the cross-sectional design of our study, as VEGF-D levels seem to fluctuate during hospital stay [ 28 ]. However, VEGF-A, a strong permeability-inducing factor related to disease severity and survival in sepsis [ 30 ], correlated positively with disease severity and ARDS development in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that chloroquine should not be used together with moxifloxacin. The combination of macrolides and fluoroquinolones can prolong QT interval.Cytokine Storm Induced by SARS-CoV-2 and the Drug Therapy methods are shown in Table 2 [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] .…”
Section: Covid-19 May Results In Cardiac Injury Via Several Mechanismsmentioning
confidence: 99%
“…70 Significantly higher VEGF concentrations were observed in COVID-19 patients compared with healthy controls, and it was shown as an important indicator related to the severity of COVID-19. 71 Bevacizumab, an anti-VEGF monoclonal antibody, is being evaluated in hospitalized COVID-19 patients at the dose level consistent with the approved doses in oncology indications for bevacizumab. The kallikrein-kinin system is a zymogen system that is known to lead to the release of the nonapeptide bradykinin after activation.…”
Section: Other Immunomodulatory Therapiesmentioning
confidence: 99%